2017
DOI: 10.1200/jco.2017.35.15_suppl.4015
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of AG-120, an IDH1 mutant enzyme inhibitor: Results from the cholangiocarcinoma dose escalation and expansion cohorts.

Abstract: 4015 Background: Mutations in the metabolic enzyme isocitrate dehydrogenase 1 (mIDH1) occur in patients (pts) with cholangiocarcinoma (CC) and are detected in up to 25% of intrahepatic CC. mIDH1 produce the oncometabolite, D-2-hydroxyglutarate (2-HG), resulting in epigenetic and genetic dysregulation and oncogenesis. AG-120 is a first-in-class, potent, oral inhibitor of mIDH1 tested in this phase I study in mIDH1 solid tumors, including CC. Methods: AG-120 was escalated in a 3+3 design from 100 mg twice daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 0 publications
2
65
0
Order By: Relevance
“…AG-120 is a first-in-class, potent, oral inhibitor of mutant IDH1 and was examined in a phase 1 study in mutant IDH1 solid tumors including iCCA. (42) AG-120 was well tolerated, and of the 73 patients with IDH1 mutant advanced CCA enrolled, 72 were evaluable for efficacy. Six percent (n = 4) had a confirmed partial response, and 56% (n = 40) experienced stable disease.…”
Section: Molecular Targeting and Immunotherapy: Idh Fgfr And Immunementioning
confidence: 99%
“…AG-120 is a first-in-class, potent, oral inhibitor of mutant IDH1 and was examined in a phase 1 study in mutant IDH1 solid tumors including iCCA. (42) AG-120 was well tolerated, and of the 73 patients with IDH1 mutant advanced CCA enrolled, 72 were evaluable for efficacy. Six percent (n = 4) had a confirmed partial response, and 56% (n = 40) experienced stable disease.…”
Section: Molecular Targeting and Immunotherapy: Idh Fgfr And Immunementioning
confidence: 99%
“…A phase II study in patients with fibroblast growth factor receptor (FGFR)‐altered advanced BTC found impressive antitumour activity of BGJ398 (a selective pan‐FGFR kinase inhibitor), with a disease‐control rate of 82%, and a manageable safety profile . An interim analysis of data from BTC with isocitrate dehydrogenase (IDH) mutation showed a disease‐control rate of 62% with IDH inhibitor …”
mentioning
confidence: 99%
“…Ivosidenib had an acceptable tolerability profile, with only few dose reductions or discontinuations due to toxicities noted in the phase 1 trial; the most frequent side effects encountered in the AML population were diarrhoea, leucocytosis, febrile neutropenia, nausea, fatigue, QT prolongation, pyrexia and anaemia [77]. In the cholangiocarcinoma cohort of the same trial, the most frequent side effects of ivosidenib reported were fatigue, nausea, diarrhoea, abdominal pain, decreased appetite and vomiting [78,79]. The chondrosarcoma patients experienced decreased appetite, long QT, nausea, anaemia and peripheral oedema [80].…”
Section: Toxicity Profile Of Idh Inhibitorsmentioning
confidence: 93%